Conflict Communication of the Majlis Shalawat: Application of Conflict Communication Models using Islamic Principles - Kriyantono, Rachmat; Luthfiyanti, Diyas Adibah (Universitas Brawijaya, 2026)
Several communication researchers have considered it important to explore religious values in conflict communication. This article is important for the field of conflict communication studies because it presents a model of conflict communication through mediation and interaction that uses Islamic principles. This paper uses ethnographic methods. Qualitative data obtained through observations of the Majelis Mahabbatur Rosul and interviews with seven informants. The results of this study indicate that conflict communication can be carried out in interpersonal and group contexts. Islam mandates the selection of a mediator whose function is to convey mauidhotil khasanah. In addition, it is also important to create an organizational culture that applies Islamic principles (1) ta'awun, (2) sabr, (3) al-ta'akhi, (4) husnal-dhann.